Inflammatory Bowel Disease and Thrombosis - Tezel, Ahmet (Galenos Publishing, 2012)
Inflammatory Bowel Disease (IBD) is a group of chronic and relapsing inflammatory disorders of the gastrointestinalsystem. In these cases, findings are detected in extraintestinal systems also. There is a tendency for thrombotic eventsin IBD, as in the other inflammatory processes. The pathogenesis of this thrombotic tendency is multidimensional,including lack of natural anticoagulants, prothrombotic media induced via the inflammatory process, long-termsedentary life style, steroid use, surgery, and catheter placement. The aim of this review was to highlight the positiverelationship between IBD and thrombotic events, and the proper treatment of at-risk patients.